2018
DOI: 10.1007/s00284-018-1521-1
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Actinosynnema pretiosum X47, An Industrial Strain that Produces the Antibiotic Ansamitocin AP-3

Abstract: Ansamitocins are extraordinarily potent antitumor agents. Ansamitocin P-3 (AP-3), which is produced by Actinosynnema pretiosum, has been developed as a cytotoxic drug for breast cancer. Despite its importance, AP-3 is of limited applicability because of the low production yield. A. pretiosum strain X47 was developed from A. pretiosum ATCC 31565 by mutation breeding and shows a relatively high AP-3 yield. Here, we analyzed the A. pretiosum X47 genome, which is ~8.13 Mb in length with 6693 coding sequences, 58 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…generated a high AP-3 yield A . pretiosum ATCC 31565, in which the production of AP-3 increased up to 19.7-fold [ 18 ]. Although mutagenesis has shown advantages in obtaining new strains, completely random mutations in the host genome critically dampen the subsequent screening efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…generated a high AP-3 yield A . pretiosum ATCC 31565, in which the production of AP-3 increased up to 19.7-fold [ 18 ]. Although mutagenesis has shown advantages in obtaining new strains, completely random mutations in the host genome critically dampen the subsequent screening efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional mutagenesis and specific gene modification represent two major ways to obtain AP-3 high-yield strains. By traditional methods, high-yield strains can be obtained by physical irradiation- and compound-induced mutagenesis [ 17 , 18 ]. However, mutations are usually accompanied by unexpected randomness, which makes it difficult to achieve precise control of the direction of evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Actinosynnema pretiosum X47 in this study was derived from A. pretiosum subspecies auranticum ATCC 31565. The genome of A. pretiosum X47 was about 8.13 Mb in length, with an average GC content of 73.91%, and 7029 genes were predicted, including 45 pairs of putative two-component signal transduction system (TCS), 13 histidine kinases, and 38 orphan response regulators ( Zhong et al, 2019 ). The morphological development of A. pretiosum is complex and similar to that of Streptomyces .…”
Section: Introductionmentioning
confidence: 99%
“…Although PhoPR is essential for the normal growth and metabolism of a broad range of species, the regulatory functions and mechanisms of PhoP differ in different bacteria. In this study, the PhoPR homolog was identified in the genome of the A. pretiosum X47 strain ( Zhong et al, 2019 ), and a phoP mutant strain was constructed. Our data suggest that deletion of phoP accelerates the formation of aerial mycelia and spore formation in strain X47, contributing to a better understanding of developmental regulation in A. pretiosum strains.…”
Section: Introductionmentioning
confidence: 99%
“…Although species in this genus are limited, Actinosynnema -origined natural products exhibit a number of biological and pharmacological activities, such as antitumor (ansamitocin [ 4 , 5 , 6 , 7 ], dnacin B1 [ 8 ] and actinosynneptides [ 9 ]), antibacterial (nocardicins [ 10 ]), anti-fungi (validoxylamine A [ 11 ]), metalloprotease inhibitor (propioxatin [ 12 ]), and siderophore (mirubactin [ 13 ]) ( Figure 1 A). Its promising application in pharmacy promoted the sequencing of the completed genome of four Actinosynnema strains (including two type strains) [ 14 , 15 , 16 , 17 ], which not only boosted the titer optimization of bioactive products by systematic metabolic engineering, but also facilitated the discovery of the Actinosynnema -derived antibiotics and dissection of their biosynthetic machineries.…”
Section: Introductionmentioning
confidence: 99%